Development of PCR-RFLP and DNA barcoding plastid markers for yellow toadflax and Dalmatian toadflax - Boswell, Andrew, author; Ward, Sarah, advisor; Sing, Sharlene, committee member; Simmons, Mark, committee member; Richards, Chris, committee member (Colorado State University. Libraries, 2013)
Yellow toadflax and Dalmatian toadflax are problematic invasive plant species in North America. Yellow toadflax was introduced multiple times to the United States from Europe, beginning in the late 1600s. Dalmatian toadflax has similarly been repeatedly introduced to the United States, starting in 1874. Both species are known to inhabit disturbed areas, competing for limiting resources with native plant species. Both are obligate outcrossed species, which allows them to maintain a high level of genetic diversity. Both species are known to inhabit a wide range of ecosystems. Yellow toadflax and Dalmatian toadflax are difficult species to control with herbicide. The most effective herbicides currently available have a 61% - 95% control rate for Dalmatian toadflax and only a 35% - 69% control rate for yellow toadflax. Herbicides that can not achieve 100% control in a population may select for resistant individuals. Biocontrol agents, specifically Mecinus janthinus, have proven to be effective for controlling invasive toadflax, to some extent. Hybridization between these two outcrossed species has occurred spontaneously under North American field conditions, and the resulting fertile hybrid progeny exhibit heterosis. Neither herbicide nor biocontrol agent effectiveness has been determined for these toadflax hybrids. Gene flow between these two species could cause introgression of advantageous traits, thus making either of these problematic species even more difficult to control. Plastid DNA PCR-RFLP and DNA barcoding markers were therefore developed to track this gene flow. One PCR-RFLP marker (trnT/D digested with Alu1) and two DNA barcoding regions (matK and trnL-F) were discovered to distinguish between cpDNA haplotypes for yellow toadflax and Dalmatian toadflax. Testing on individual plants collected from multiple U.S. field hybridization sites has revealed that yellow toadflax chloroplast DNA occurs more frequently in hybrids than Dalmatian toadflax cytoplasm. These results indicate that gene flow is asymmetric in persistent L. vulgaris x L. dalmatica populations.
Keywords: PCR-RFLP; DNA barcode; Dalmatian toadflax; Yellow toadflax